The First Case of Yersinia Pestis Subsp. Pestis Isolation in the Territory of Altai Mountain Natural Plague Focus. Communication 1. Microbiological Characteristics, Molecular-Genetic and Mass-Spectrometric Identification of the Isolate - S. V. Balakhonov (Проблемы особо опасных инфекций, 2013)
Performed is a complex microbiological, molecular-genetic and mass-spectrometric identification of Yersinia pestis main ssp. strain, which was isolated for the first time in the history of surveillance over the Altai mountain natural plague focus in June, 2012. Determined is its high universal virulence. Plasmid screening, multi-locus VNTR- and mass-spectrometric analyses have revealed the strain to be more closely related to the plague agent variant, circulating in the territory of the natural focus Khuukh-Serkh-Munkh-Khairkhan, Bayan-Ul’giisk aimak, Mongolia.